STUDY ON THE CONSUMER ACCEPTANCE OFDIM SUM OF FISHERIES PRODUCTS (Squid and White Shrimp) - Esti P. Sari; Dewita Dewita; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aims to determine the study of consumer acceptanceof fishery dim sum (squid and white shrimp). The method used was experimental, by comparing the dim sum of squid (Loligo sp.) With white shrimp dim sum (Litopenaeus vannamei). This research was conducted to test organoleptic (appearance, aroma, taste and texture) and proximate analysis (moisture, protein, ash and fat content) of the resulting dim sum products. Based on the observed parameters for squid dim sum and white shrimp dim sum, the best preference test is in treatment A2 (white shrimp dim sum) with consumer preference level of 100% from 80 panelists with attractive characteristics of bright white and slightly clean appearance. yellowish, more distinctive taste of shrimp dim sum, specific aroma of shrimp and soft texture. The average value of the organoleptic assessment on A2 treatment is Fine 8.21, aroma 8.11, taste 8.38 and texture 8.26 and the resulting proximate analysis is the water content of 59.34%, protein content 33.65 %, ash content 1.31% and fat content 1.70%. Keywords: Dim sum, squid, white shrimp,Organoleptic, Parameters, Proximate